STRATEGI PEMENANGAN TENGKU ZULKENEDI YUSUF DALAM MEMPEROLEH KURSI ANGGOTA DPRD KABUPATEN KEPULAUAN MERANTI TAHUN 2019-2024 - Zukhron, Ahmad; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Strategy is one of the keys to victory for a candidate or candidate who plays a very important role in the legislative election victory. Political strategy is a method of winning the fight from various political forces that want power. This political strategy was formed from the impact of a reform process that occurred in which the political process was more diverse. The winning strategy is carried out to increase the number of people in choosing related candidates. For this reason, in winning the competition between candidates, competition between candidates is by making a political strategy. This research is about the winning strategy carried out by Tengku Zulkenedi Yusuf in obtaining a seat as a member of the DPRD of the Meranti Islands Regency. Tengku Zulkenedi Yusuf is the youngest candidate from the PKS party to be elected as a member of the DPRD of the Meranti Islands Regency.This study aims to determine the winning strategy of Tengku Zulkenedi Yusuf in obtaining seats for members of the Meranti Islands Regency DPRD in 2016 and to describe the factors that drive Tengku Zulkenedi Yusuf's winning strategy in obtaining seats for members of the DPRD Islands Meranti Regency in 2019. The method used is used in this study is a descriptive qualitative approach. Sources of research data include primary and secondary data sources, tools and techniques for collecting data using interviews and documentation.The results in this study reveal that Tengku's winning strategy Zulkenedi Yusuf, namely Forming new voters from young people. Conducting campaigns by going directly to the field, namely focusing on Tebing Tinggi District. Inviting various communities engaged in sports, arts and economics in Tebing Tinggi District. Conducting campaigns using mass media. Meanwhile, the supporting factors in the winning strategy of Tengku Zulkenedi Yusuf are the first factors branding. Second, promotion delivers the programs that will be offered. Third, capital, namely in the form of funds issued. Fourth, placement.Keywords: General Election, Strategy, Political Marketing, Young Candidates.